Hubungan Aktivitas Menghafal Al-Qur’an Dengan Social Quotient Santri di Pondok Pesantren Putri Walisongo Cukir Jombang - Ida Nikmatu Alfin; Solihul Anshori (LPPM STIT Miftahul Ulum Bangkalan, 2020)
Starting from the time of the Prophet Muhammad SAW until now Memorizing the Al-Qur'an is the most powerful effort to maintain the truth of the Al-Qur'an. Social Quotient or what is commonly interpreted as social intelligence states that a person's ability to be able to properly understand what other people feel. The focus of this research is formulated into problem formulations which include: 1) How do students memorize Al-Qur'an activities at the Walisongo Cukir Jombang Islamic Boarding School 2) How the Social Quotient of the students at the Pondok Pesantren Putri Walisongo Cukir Jombang, 3) How is the relationship between memorizing Al -Qur'an with Social Quotient students at the Walisongo Cukir Jombang Islamic Boarding School. The approach of this research is a quantitative approach and the type of research uses correlational with the design in the form of ex post facto. Based on the research, it was found that based on the X variable (Al-Qur'an memorizing activity) of the students at the Walisongo Cukir Jombang Islamic Boarding School, the percentage of students whose value is less than / equal to an average of 40% and the percentage of students whose value is more than / equals an average of 60%. Based on the Y (Social Quotient) variable of students at the Walisongo Cukir Jombang Islamic Boarding School, the percentage of students whose scores are less than / equal to the average is 52% and the percentage of students whose scores are more than / equal to the average of 48%. The results of the analysis showed that there was no positive and significant relationship between memorizing Al-Qur'an activities with the Social Quotient of students at the Walisongo Islamic Boarding School, Cukir Jombang.